The Effect of Self Hypnosis on Anxiety of Pregnant Women in the Third Trimester at TPMB Sahabat Ibu, Malang Regency - Feva Tridiyawati; Wiwin Sofarida; Nadia Devisa Azhari; Nur Inayah; Ririn Indrawati; Siti Maemunah (Jurnal Penelitian Pendidikan IPA, 2025)
Pregnancy represents a profound physiological and psychological transition, often accompanied by significant discomfort, particularly during the third trimester. This discomfort, in turn, frequently triggers heightened levels of anxiety among expectant mothers. Pregnancy-related anxiety is a pervasive psychological condition, as highlighted by data from the WHO in 2015, which indicated that approximately 10% of pregnant women and 13% of postpartum women worldwide experience mental health disorders, including trauma and depression. Elevated anxiety during pregnancy poses considerable risks to both maternal and fetal health. This study aims to evaluate the effectiveness of self-hypnosis in reducing anxiety levels among third-trimester pregnant women. A pre-experimental design with a one-group pretest-posttest approach was applied, involving 40 pregnant women experiencing anxiety. Statistical analysis using the Wilcoxon signed-rank test revealed a significant reduction in anxiety levels following the self-hypnosis intervention (p = 0.000; p < 0.05). These findings highlight self-hypnosis as an effective, non-invasive, and accessible therapeutic approach for improving maternal psychological well-being, with potential benefits for both maternal and fetal health.